Relationship Blood Gas Analysis And Hemostasis Physics In Multiple Trauma Patients In Adam Malik Hospital Medan - Karim, T. Abdul; Wijaya, Dadik Wahyu; Irina, Rr Sinta (CoinReads Media Prima, 2023)
Introduction: Trauma is currently the most common cause of death in the first four decades of life and is still a major public health problem in every country. Arterial blood gas analysis (AGDA) is known to be an important marker for poor patient outcomes and occult or compensatory hypoperfusion. This study also evaluated the relationship and influence of AGDA scores on the outcome and prognosis of patients with multiple trauma. The results of this study will be able to assist in the rapid triage of acute trauma patients, which will also help identify high-risk patients who develop severe complications. Method: This study assessed the relationship between initial arterial blood gas and initial hemostatic function in acute trauma patients who came to the emergency department at H. Adam Malik General Hospital Medan. This type of research is a retrospective analytic where data is taken from medical records to see the relationship between AGDA and coagulation profile in multiple trauma patients at H. Adam Malik General Hospital Medan. After recruiting research samples at Adam Malik Haji Center General Hospital Medan, it was found that 141 multiple trauma patients who underwent surgery at H. Adam Malik General Hospital Medan met the inclusion criteria and were not included in the exclusion criteria Results: In this study, there were significant results between the pH and the three hemostatic physiology, there were no significant results between pCO2 and the three hemostatic physiology, and there were significant results between the HCO3 value and the PT and INR values, but no significant results were obtained with the APTT. Some authors believe that arterial PCO2 at admission is a significant prognostic factor in patients with traumatic head injury, but several studies dispute the arterial blood gas (ABG) parameter as a reliable indicator of short-term outcome in these patients. The main goal of the management of critically ill patients is the maintenance and optimization of cellular (and organ) health. Conclusion: This goal can be achieved by maintaining oxygenation, perfusion, fluid, electrolyte, and acid-base balance. Acid-base and oxygenation disorders are also critical, especially when these disorders develop rapidly.